1998
DOI: 10.1590/s0100-879x1998001200010
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of T cell response to leishmania antigens by determinants of histocompatibility leukocyte class I and II molecules

Abstract: It has been shown that HLA class I molecules play a significant role in the regulation of the proliferation of T cells activated by mitogens and antigens. We evaluated the ability of mAb to a framework determinant of HLA class I molecules to regulate T cell proliferation and interferon gamma (IFN-γ) production against leishmania, PPD, C. albicans and tetanus toxoid antigens in patients with tegumentary leishmaniasis and healthy subjects. The anti-major histocompatibility complex (MHC) mAb (W6/32) suppressed ly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2005
2005
2006
2006

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…In Brazil, an increase in the expression of HLA-DR antigens was found in patients infected by Leishmania chagasi [55]. Also in Brazil, Bacellar et al (1998) suggested that the HLA class I antigens are capable of suppressing the proliferation and secretion of cytokines by T lymphocytes in the immune response against Leishmania antigens [56].…”
Section: Parasitic Infectionsmentioning
confidence: 99%
“…In Brazil, an increase in the expression of HLA-DR antigens was found in patients infected by Leishmania chagasi [55]. Also in Brazil, Bacellar et al (1998) suggested that the HLA class I antigens are capable of suppressing the proliferation and secretion of cytokines by T lymphocytes in the immune response against Leishmania antigens [56].…”
Section: Parasitic Infectionsmentioning
confidence: 99%
“…Their last immunization with TT occurred between 6 and 24 months before blood collection. PBMC were stimulated with 5 limit of flocculation (LF)/ml [11], supernatants were harvested, and cytokine production was measured by ELISA.…”
Section: Tetanus Toxoid-immunized Individualsmentioning
confidence: 99%